Endocrine lineage biases arise in temporally distinct endocrine progenitors during pancreatic morphogenesis - Marissa A. Scavuzzo (Nature Portfolio, 2018)
Endocrine progenitors form early in pancreatic development but the diversity of this cell population is unclear. Here, the authors use single cell RNA sequencing of the mouse pancreas at e14.5 and e16.5 to show that endocrine progenitors are temporally distinct and those formed later are more likely to become beta cells